Post-rift vertical movements of the southern African passive margins since 130 Ma : a combined approach : basin analysis, landforms study - (:unkn) unknown (My University, 2017)
The South African (Kalahari) Plateau is the world's largest non-orogenic plateau. It forms a large-scale topographic anomaly (×1000 km) which rises from sea level to > 1000 m. Most mechanisms proposed to explain its elevation gain imply mantle processes. The age of the uplift and the different steps of relief growth are still debated. On one hand, a Late Cretaceous uplift is supported both by thermochronological studies and sedimentary flux quantifications. On the other hand, geomorphological studies suggest a Late Cenozoic uplift scenario (<30 Ma). However few attentions were paid to the evolution of the overall geomorphic system, from the upstream erosional system to the downstream depositional system. This study is based on two different approaches : onshore, on the mapping and chronology of all the macroforms (weathering surfaces and associated alterites, pediments and pediplains, incised rivers, wave-cut platforms) dated by intersection with the few preserved sediments and the volcanics (mainly kimberlites pipes) ; offshore, on a more classical dataset of seismic lines and petroleum wells, coupled with biostratigraphic revaluations (characterization and dating of vertical movements of the margins - sediment volume measurement). The main result of this study is that the South African Plateau is an old Upper Cretaceous relief (90-70 Ma) reactivated during Oligocene (30-15 Ma) times. Its evolution can be summarized as follows : 100-70 Ma (Cenomanian to Campanian): low elevation plateau (0-500 m) with older and higher reliefs located along the Indian side, acting as a main divide between the Atlantic and the Indian Oceans. First uplift occurred in the east at ~92 Ma, with a fast flexuration of the Indian margins. This initiates a paroxysm of the erosion (90-80 Ma) with the growth of a large delta along the Atlantic margin (Orange delta). Deformation migrated progressively westward and resulted on the growth of the Atlantic marginal bulg
Keywords: African Research